2011
DOI: 10.1111/j.1365-2249.2011.04394.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-9+ IL-10+ T cells link immediate allergic response to late phase reaction

Abstract: SummaryThe mechanism underlying late-phase allergic reactions (LPR) remains incompletely understood. This study aimed to investigate the role of a newly described subset of T cells, interleukin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Therefore, to study bona fide T H 9 cells in vivo , IL-9 was stained against a dump gate excluding IL-17A, FoxP3 and IL-4. Consistent with a previous study (19), multiple subcutaneous ovalbumin/alum immunisations in BALB/c mice, a classic type-2 priming model that leads to formation of T H 2 cells and IgE (19), also led to generation of T H 9 cells (CD3 + CD4 + IL-4 − IL-17A − FoxP3 − IL-9 + ) that could be detected in draining lymph nodes (Fig 4a). Analysis of chemokine receptor expression on these T H 9 cells supported in vitro observations as T H 9 cells generated in this model expressed CCR3, CCR6 and CXCR3 (Fig 4b).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, to study bona fide T H 9 cells in vivo , IL-9 was stained against a dump gate excluding IL-17A, FoxP3 and IL-4. Consistent with a previous study (19), multiple subcutaneous ovalbumin/alum immunisations in BALB/c mice, a classic type-2 priming model that leads to formation of T H 2 cells and IgE (19), also led to generation of T H 9 cells (CD3 + CD4 + IL-4 − IL-17A − FoxP3 − IL-9 + ) that could be detected in draining lymph nodes (Fig 4a). Analysis of chemokine receptor expression on these T H 9 cells supported in vitro observations as T H 9 cells generated in this model expressed CCR3, CCR6 and CXCR3 (Fig 4b).…”
Section: Resultssupporting
confidence: 92%
“…To generate T H 9 cells under allergic conditions, BALB/c mice were immunised subcutaneously in hind flanks with 100µg type IV ovalbumin (OVA) (Sigma) in 100µL aluminium hydroxide gel (Sigma) on days 0, 3 and 7 as previously described (19). 7 days following final sensitisation, mice were administered chemokine receptor antagonists (in 250µL endotoxin-free PBS) intravenously: 250µg MCP ala/ala (scrambled peptide control) (20, 21), 100µg CCL20 6–70 (CCR6 antagonist) (21), 250µg CXCL11 4–79 (CXCR3 antagonist) (20), 250µg SB-328457 (CCR3 antagonist; Tocris Bioscience) (22) or PBS + 0.01% Tween 80 (vehicle for SB-328457).…”
Section: Methodsmentioning
confidence: 99%
“…The immediate hypersensitivity reaction can be followed by a T‐cell‐mediated late phase response, which occurs 12–48 h after antigen exposure and is caused by the continuous presence of antigen . During this late phase reaction, Th2 cells and intestinal epithelial cells keep producing Th2‐related cytokines such as IL‐4, IL‐5, IL‐9, and IL‐13 .…”
Section: Food Allergy Through Broken Tolerancementioning
confidence: 99%
“…34 It may be speculated that memory Th9 cells exist and provide immediate high levels of IL-9 upon receiving the re-stimulation. It is also of interest that He et al 48 observed an abundance of Th9 cells in the jejunum of mice developing allergic response in that tissue 48 hours following the initiation of the response. These authors suggested, therefore, that Th9 cells serve as a link between immediate and late-phase allergic response.…”
Section: Commentsmentioning
confidence: 99%